Управління інтуїцією: ресурс успішності лідерів бізнесу - Чернявська, Тетяна Павлівна (НТУ "ХПI", 2010)
The article is devoted research of intuition as a basic resource of success of leaders in business. The theoretical analysis of modern conceptions of business-intuition allowed to ground methodological and instrumental bases of exposure and development of intuition of subjects of business-activity. The program of the specialized psychological training is presented "Management of business-intuition".
Keywords: теоретико-методологічне обґрунтування; інтуїція; регуляція